Assessing Infrastructure to Care for Pediatric Patients in the Prehospital Setting. Issue 6 (June 2020) - Ely, Michael; Edgerton, Elizabeth A.; Telford, Russell; Page, Kent; Hemingway, Craig; Vernon, Donald; Olson, Lenora M.
Abstract : Objectives: Pediatric patients represent a small proportion of emergency medical services (EMS) calls, challenging providers in maintaining skills in treating children. Having structural capacity to appropriately diagnose and treat pediatric patients is critical. Our study measured the availability of off-line and on-line medical direction and recommended pediatric equipment at EMS agencies. Methods: A Web-based survey was sent to EMS agencies in 2010 and 2013, and results were analyzed to determine availability of medical direction and equipment. Results: Approximately 5000 agencies in 32 states responded, representing over 80% response. Availability of off-line medical direction increased between years (78% in 2010 to 85% in 2013), was lower for basic life support (BLS) (63% and 72%) than advanced life support (ALS) agencies (90% and 93%), and was generally higher in urban than rural or frontier locations. On-line medical direction was consistently available (90% both years) with slight increases for BLS agencies (87% to 90%) and slightly greater availability for urban and rural compared with frontier agencies. The majority of agencies carried most recommended equipment; however, less than one third of agencies reported carrying all equipment. Agencies with off-line medical direction, on-line medical direction, and with both off-line and on-line medical direction were respectively 1.69, 1.31, and 2.21 times more likely to report carrying all recommended equipment. Conclusions: Basic structural capacity exists in EMS for treating children, with improvements seen over time. However, gaps remain, particularly for BLS and nonurban agencies. Continuous attention to infrastructure is necessary, and the recent development of national performance measures should further promote quality emergency care for all children. Abstract : Supplemental digital content is available in the text.